Stream and well water samples from two rural communities in Ekiti State, Nigeria: assessment of physicochemical parameters, bacteriological quality and public health significance (Acta Scientiarum. Biological Sciences, 2023)
Infectious diseases caused by microorganisms are widespread health risks associated with drinking water. This study evaluated the physicochemical parameters and bacteriological quality of the stream and well water using standard protocols. The bacteria were identified by conventional and molecular methods. Antibiotic susceptibility and location of antibiotic resistance markers (ARMs) were determined using disc diffusion and acridine orange, respectively. The highest mean Total Heterotrophic Bacterial Counts (THBC), Total Coliform Counts (TCC) and Faecal Coliform Counts (FCC) from the stream water was 4.3 ± 0.3Ã—106, 8.9 ± 0.0Ã—105, and 3.5 ± 0.1Ã—104 (CFU mL-1), respectively. The well water had mean TCC ranging between 2.8 ± 0.0Ã—103 and 2.1 ± 0.1Ã—104 (CFU mL-1). Six bacterial genera: Staphyloccocus, Pseudomonas, Escherichia, Enterobacter, Klebsiella, and Shigella were isolated. The mean temperature of the water ranged from 26.0 ± 0.3oC to 27.0 ± 0.1oC. The highest mean dissolved oxygen, total hardness, sulphate and magnesium was 24.0 ± 1.0, 40.1 ± 0.8, 11.0± 1.0, and 67.0 ± 1.5 (mg L-1), respectively. The results showed that â‰¥ 66.7 S. aureus were Levofloxacin and Streptomycin sensitive; between 45.5 and 68.1% of the isolates were Gentamycin and Chloramphenicol resistant, while 81.8% exhibited multidrug resistance. Escherichia coli EcSW3, E. aerogenes EeWW2, K. pneumoniae KpSW3, and S. aureus SaSW had their entire ARMs located on the plasmids with the molecular sizes Ë‚ 2.027 Kbp. This study showed that the stream and well water harboured bacteria with some ARMs on plasmids, indicating the possibility of horizontal transfer of antibiotic-resistant genes among the bacteria. In addition, it showed the necessity to enlighten the rural populace on the importance of cleaning the surroundings near water sources so as to prevent water-borne diseases.